EXISTENCE OF TERAPEUTIC AGREEMENTS AS BASICS OF RELATIONSHIP DOCTORS AND PATIENTS IN HEALTH SERVICES - Sarsintorini Putra; Anggraeni Endah Kusumaningrum (UNTAG Law Review, 2019)
This work aims to analyze the existence of a therapeutic agreement as the basis of the relationship between doctors and patients in health services. Health services originate from a relationship of trust between doctors and patients that develops into a therapeutic transaction or therapeutic agreement. The object of this therapeutic agreement, when viewed from medical science, can be specified in general in health services that can be started from promotive, preventive, curative, and rehabilitative efforts. Juridically, all medical action in the health service can be a legitimate object of law, but the form of the medical agreement must be clear whether the inspector is an agent (agreement on the effort) or result of the intervention (agreement on results). This is important in relation to the burden of proof in the event of a lawsuit.